Protonation states and catalysis: Molecular dynamics studies of intermediates in tryptophan synthase - Huang, Yu-ming M. (J Mol Recognit, 2014)
The importance of protonation states and proton transfer in pyridoxal 5′-phosphate (PLP)-chemistry can hardly be overstated. Although experimental approaches to investigate pKa values can provide general guidance for assigning proton locations, only static pictures of the chemical species are available. To obtain the overall protein dynamics for the interpretation of detailed enzyme catalysis in this study, guided by information from solid-state NMR, we performed molecular dynamics (MD) simulations for the PLP-dependent enzyme tryptophan synthase (TRPS), whose catalytic mechanism features multiple quasi-stable intermediates. The primary objective of this work is to elucidate how the position of a single proton on the reacting substrate affects local and global protein dynamics during the catalytic cycle. In general, proteins create a chemical environment and an ensemble of conformational motions to recognize different substrates with different protonations. The study of these interactions in TRPS shows that functional groups on the reacting substrate, such as the phosphoryl group, pyridine nitrogen, phenolic oxygen and carboxyl group, of each PLP-bound intermediate play a crucial role in constructing an appropriate molecular interface with TRPS. In particular, the protonation states of the ionizable groups on the PLP cofactor may enhance or weaken the attractions between the enzyme and substrate. In addition, remodulation of the charge distribution for the intermediates may help generate a suitable environment for chemical reactions. The results of our study enhance knowledge of protonation states for several PLP intermediates and help to elucidate their effects on protein dynamics in the function of TRPS and other PLP-dependent enzymes.